2016
DOI: 10.1177/1533034616674323
|View full text |Cite
|
Sign up to set email alerts
|

Serum Trefoil Factor 3 as a Protein Biomarker for the Diagnosis of Colorectal Cancer

Abstract: Colorectal cancer is one of the most frequent causes of cancer-related deaths worldwide. Thus, there is a need for timely diagnosis and effective treatment. Our aim in the present study was to detect the serum level of trefoil factor 3 protein and evaluate the diagnostic accuracy of trefoil factor 3 in patients with colorectal cancer. We collected serum samples from 204 participants (127 patients with colorectal cancer, 35 patients with polyps, and 42 healthy controls). The levels of serum trefoil factor 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…In this category, the more promising proteins were trefoil factor (TFF)3 [ 21 ], CA11-19 [ 22 ], a combination of insulin-like growth factor binding protein 2 (IGFBP2), Dickkopf-3(DKK3), and pyruvate kinase M2 (PKM2) [ 23 ] and DC-SIGN/DC-SIGNR [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this category, the more promising proteins were trefoil factor (TFF)3 [ 21 ], CA11-19 [ 22 ], a combination of insulin-like growth factor binding protein 2 (IGFBP2), Dickkopf-3(DKK3), and pyruvate kinase M2 (PKM2) [ 23 ] and DC-SIGN/DC-SIGNR [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is thought to promote invasion of cells by acting directly on the cells and indirectly on the vasculature. Results from the study by Li et al showed a sensitivity of 74.2% and specificity of 94.8%; however, the level of this marker in polyps is not significantly different from that in the CRC cohort, making this less likely to be a useful diagnostic test [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…To discover urinary diagnostic biomarkers for CRC, we thoroughly searched the previous literature on serum protein biomarkers for the diagnosis of CRC using PubMed, and identified 6 small protein biomarker candidates with a high AUC and high accuracy: Cyr 61, TFF3, IGFBP3, ANGPTL2, SERPINA1 and EFEMP2 [15], [16], [17], [18], [19], [20]. Based on the results from the literature search, we analyzed urinary protein concentrations of these 6 proteins in the training cohort, using quantitative mono-specific ELISAs.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between TFF3 and mucins has also been reported to protect intestinal epithelia from injuries, maintaining mucosal barrier function (26). Furthermore, mitogenic effects of TFF3 have been identified in vitro in primary cell culture, and TFF3 has been demonstrated to inhibit apoptosis, induce cellular invasion, act as an inflammatory modulator and exhibit pro-angiogenic activity (27)(28)(29)(30)(31)(32). A protective or healing effect of TFF3 has also been reported in a series of experiments, such as cells in vitro, mice, rats and human (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%